Karakteristik dan Kualitas Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Limbah Cair Rumah Sakit (Studi Deskriptif di Rumah Sakit X Kabupaten Jeneponto) - Karini, Tri Addya; Wijaya, Dian Rezki; Arranury, Zil Fadhillah (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Hospital waste treatment is part of the hospital environmental sanitation efforts, the goals is to protecting the public from the dangers of environmental pollution from hospital wastewater and preventing the increase in nosocomial infections in the hospital environment, because it is known that hospital waste can contain potential dangers that are infectious, toxic and radioactive. This type of research is observational analytic in a descriptive approach to determine the quality of wastewater at the hospital X District of Jeneponto in 2020. Conducted at the hospital X Jeneponto Regency in June-July 2020. The sampling technique used was purposive sampling technique. The sample in this study was wastewater originating from 2 points, namely the inlet and outlet of WWTP, the sampling technique and the frequency of sampling were 2 times, namely on the day Friday morning and afternoon, for 1 Day. The parameters measured in this study were temperature, pH, BOD and COD. Based on the results of laboratory examinations of wastewater samples at the hospital X, Jeneponto Regency, can draw the conclusion that temperature, pH and BOD levels, still meet different requirements The COD level value at the inlet during the daytime sampling with a value of 74.0567 mg / l does not meet the requirements according to the Liquid Waste Water Quality Standard. Hospital based on the Regulation of the Governor of South Sulawesi Number: 69/2010 concerning Quality Standards and Criteria for Environmental Damage Appendix II Point D.3 Wastewater Quality Standards for Hospital Activities (COD = 70 mg / l). The BOD and COD of hospital X wastewater, it is hoped that the hospital management and management will allocate the operational funds needed in order to maintain the Wastewater Treatment Plant, especially in aerobic / anaerobic tanks as well as filtration and check the quality of wastewater every time. Every 6 months to find out how much influence the waste water has on the hospital environment and its surroundings. Keywords : waste management, wastewater, hospital, environment